The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/1980-5373-mr-2018-0682
|View full text |Cite
|
Sign up to set email alerts
|

A New methodology of Nondestructive Testing for Quantitative Evaluation of Sigma Phase in Duplex Stainless Steels

Abstract: Duplex Stainless Steels (DSSs) are widely used in the oil and gas industry. When the steel is subjected to a thermal gradient, as in welding may occur precipitation of intermetallic phases. Among these phases, there is the sigma phase, which even in small quantities reduces drastically the mechanical and corrosion resistance properties. According to some studies in the literature, the limit amount of sigma phase present in steel in welded joints must be in a maximum volume fraction of 2,5%. In search to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The KOH concentration used for this analysis confirm the suitable condition (pH 13.97), as already described by (HASKEL et al, 2015;HASKEL et al, 2019;DE SAMPAIO et al, 2020), for a selective interaction with the intermetallic phase.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The KOH concentration used for this analysis confirm the suitable condition (pH 13.97), as already described by (HASKEL et al, 2015;HASKEL et al, 2019;DE SAMPAIO et al, 2020), for a selective interaction with the intermetallic phase.…”
Section: Resultssupporting
confidence: 70%
“…Electrolytic solutions like KOH, NaOH presents high sensibility for reaction with Cr in the σ and χ phases that is oxidized to higher states (Cr +3 to Cr +6 ). This selective behaviour is an advantage to be used for metallographic and potentiodynamic tests (HASKEL et al, 2019;DE SAMPAIO et al, 2020). From the results obtained by (HASKEL et al, 2019), electrochemical cells with micro electrode concepts with seems to be better for the analysis, providing current densities in the order of microamperes and an outstand sensitivity result for small levels of σ and χ deleterious phases quantification, this has also been proved by (DE SAMPAIO et al, 2020).…”
Section: Introductionmentioning
confidence: 80%
“…Thus, the occurrence of these peaks were correlated with deleterious phases precipitated identified by LOM. Recently, Haskel et al, 61 tested several concentrations of KOH and scanning rates in UNS S31803 duplex stainless aged specimens. In this work, a sigma-free specimen was distinguished from another one aged at 870 °C, which containing 0.2% sigma, using a 3.0 mol l −1 KOH solution and a scan rate of 1.0 mV s −1 .…”
mentioning
confidence: 99%
“…Linear sweep voltammetry (LSV) is an effective technique used to detect the σ phase in DSS 18 . Haskel et al 19 used this technique to detect the χ and σ phases in DSS UNS S31803 presenting up to 0.9% intermetallic phases. Results in the aforementioned study which showed variations in charge density and current density, advocated for the feasibility of developing an on-site non-destructive technique assay.…”
Section: Introductionmentioning
confidence: 99%